Uji Aktivitas Antibakteri Ekstrak Daun Kemangi (Ocium sanctum L) terhadap bakteri Patogen dengan metode KLT Bioautografi - Dewi, Hasna (Journal of Pharmacy Tiara Bunda, 2023)
A research of the antibacterial activity test extracts of basil (Ocimum sanctum L) against pathogenic bacteria by using KLT Bioautografi. This study aims to determine the activity and basil leaf extract chemical components are on the inhibition of bacterial. Basil (Ocimum sanctum L) extracted by maceration method using ethanol 70%. Extraction then screened for antibacterial activity with levels of 1 mg / ml against microbes that Staphylococcus aureus, Streptococcus mutans, Staphylococcus epidermidis, Salmonella typhi, Bacillus subtillis, Escherichia coli, Pseudomonas aeruginaosa and vibrio sp. Tests showed that 70% ethanol extract of leaves of basil can inhibit the growth of Staphylococcus aureus, Streptococcus mutans, Salmonella typhi, Bacillus subtillis, Escherichia coli, Pseudomonas aeruginaosa and vibrio coma. Testing TLC-Bioautografi basil leaves ethanol extract using ethyl acetate eluent: n-hexane (1: 3) showed inhibition of bacteria at Rf values of 0.15, 0.31, 0.44. Identification test showed that the compounds provide antibacterial flavonoids, alkaloids and terpenoids